Sanksi Tindak Pidana Terorisme (Studi Komparatif Undang-Undang Nomor 15 Tahun 2003 dan Fiqh Jinayah) - Huzaimah Al-Anshori (Institut Agama Islam Negeri (IAIN) Kediri, 2018)
Indonesia is often attacked by terrorism actions, it is done by a group of irresponsible people, so that the government takes out a law about terrorism which aims to minimize the terrorism criminal as early as possible. The result from the researcher that the act of terrorism criminal states on law No. 15/2003 is an action that consist of forbidden criminal act elements, as like on chapter III, section 6 to19, law No. 15/2003. In fiqh jinayah. side, the act of terrorism criminal which is included on section 6 to19 of law 15/2003 is also discussed in jarimah qat’ al-tariq, because there are similarities in criminal action. The punishment for the terrorism actor is different according to law No. 15/2003 and fiqh jinayah. There are many variations of fiqh jinayahpunishment, such as qisas, diyat and ta’zir.